How Can a Serbian History Textbook Be Used to Thoroughly Teach the Causes of the Holocaust? - Kovač, Danilo D. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
A history textbook authored by Mira Radojević, was written for history students aged 18, entering their final year of a four-year Serbian grammar school education. The textbook presents in chronological order a range of topics that canvas the seminal political events that shaped Europe and America throughout the 20th century. The textbook’s primary drawback is an absence of the learning tasks required to facilitate improved learning in relation to higher order thinking. This paper aims to overcome this issue. The manuscript does not represent empirical research; rather, it is more of a practitioner piece, with the goal of providing a framework in which the textbook can be utilised to gradually and meaningfully develop a causal analysis of the Holocaust. Four history classes, broken into a series of five steps, are designed to be used in concert with Mira Radojević’s textbook. It is however the hope that these steps will provide a framework to be used with a variety of textbooks that, like the Mira Radojević’s textbook, will focus on the historical facts rather than on causal analysis of the Holocaust and developing students’ higher order thinking.
Keywords: Holocaust education; causal analysis; classification; Serbia; textbooks; history